Association of Thrombocytopenia with Chronic Liver Disease Due to Hepatitis-C (Journal of Fatima Jinnah Medical University, 2018)
Introduction: Patients with Chronic Liver Disease (CLD) including advanced fibrosis and cirrhosis commonly experience thrombocytopenia. Thrombocytopenia associated with chronic liver disease has been reported in 15–70% of patients with advanced fibrosis and portal hypertension, depending on the stage of disease. Thrombocytopenia may be caused by Hepatitis C virus (HCV) directly, or it may result from Iinterferon based anti-viral therapy that affects platelet number or function, either directly or by suppression of thrombopoiesis in the bone marrow. Objectives: To determine the frequency of thrombocytopenia in CLD patients due to Hepatitis C virus. Material and Methods: This cross sectional study was conducted at Department of Medicine, Civil Hospital, Bahawalpur from 01-03-2013 to 28-12-2013. Non probability purposive sampling was done. The calculated sample size was 325 cases, with 5 % margin of error, 95 % confidence level. All the collected data was entered into computer software SPSS version 17 and analyzed. Results: Study results show that majority of the patients were between 41-50 years i.e. 43.69% (n=142), mean age was 38.54+5.12 years. 59.38% (n=193) were male and 40.62% (n=132) females. Frequency of thrombocytopenia in CLD patients due to Hepatitis C virus was 21.23% (n=69) while 78.77% (n=256) had no findings of thrombocytopenia. Conclusion: The frequency of thrombocytopenia is high among patients with Chronic Liver Disease (CLD). Therefore it is recommended that every patient who presents with Chronic Liver Disease should have work-up for thrombocytopenia
Keywords: Chronic Liver Disease, Thrombocytopenia, Hepatitis C Virus, Frequenc